Behaviour of post-tensioned benches made of high-content recycled aggregate concrete reinforced with racquet string fibres - Narakorn Suwannachote; Thanongsak Imjai; Fetih Kefyalew; Radhika Sridhar; Reyes Garcia; U. Johnson Alengaram; Sivakumar Naganathan (Sustainable Structures)
This study investigates the serviceability and structural behaviour of a new type of recycled aggregate concrete (RAC) bench with waste badminton racquet fibres. Twenty-one cantilever benches were tested in two Series with different fibre volume fractions (Vf = 0%, 0.5%, 1.0% or 1.5%). The RAC had 100% of natural aggregates replaced with recycled concrete aggregate (RCA). The benches in Series II were post-tensioned in flexure using an innovative Post-Tensioned Metal Strapping (PTMS) technique using 1, 2 or 3 straps. Tests were carried out to evaluate 1) static loading behaviour, 2) long-term behaviour after 365 days of sustained loading, and 3) human-induced vibrations. The static test results show that benches with 100% RAC and PTMS had higher capacity (by about 25%) that counterpart benches without PTMS. Hence, the maximum flexural strength of the cantilever bench was improved by 5.7% for the cantilever bench with PTMS strengthening, which further enhanced the flexural behaviour compared to the bench with only 1.5% of fibres. The human-induced vibration test results confirmed that the maximum vibration of the benches met the code limits for floor buildings. Finite element analyses of the RAC benches with PTMS were carried out in Abaqus®, and the experimental deflections agreed well (errors <5%) with the FEM results. A simplified fatigue life analysis confirmed that the RAC benches with PTMS can have a potential service life of up to 20 years. The use of glow-in-the-dark (GID) features into the benches in Series II enhanced their night-time visibility and visual appeal by up to 8 h. This research contributes towards the development of new applications for RAC with waste badminton racquet fibres, which can offer more sustainable solutions for the construction of urban furniture.